Synthesis, Characterization and Computational Analysis of Thiophene-2,5-Diylbis((3-Mesityl-3-Methylcyclobutyl)Methanone) - Koparir, Pelin; Omar, Rebaz Anwar; Sarac, Kamuran; Ahmed, Lana Omer; Karatepe, Arzu; Taskin-Tok, Tugba; Safin, Damir A. (Taylor & Francis Ltd, 2023)
In this work, we report synthesis, characterization and computational studies of the symmetric thiophene-based compound thiophene-2,5-diylbis((3-mesityl-3-methylcyclobutyl)methanone) (1) obtained from 2,2'-thiobis(1-(3-mesityl-3-methylcyclobutyl)ethan-1-one) and glyoxal using the Hinsberg thiophene ring synthesis approach. The Density Functional Theory (DFT) calculations were performed to probe the structure of 1, as well as its electronic and optical properties. The global reactivity descriptors, as well as molecular electrostatic potential (MEP), were revealed to probe the reactivity and to determine the reactive centers of 1. The DFT calculations were also applied to probe 1 as a potential corrosion inhibitor for some important metals used in implants. Electron charge transfer from the molecule of 1 to the surface of Ni, Au, Co, Cu, Mo, W, Fe and Cr was revealed. Bioavailability, druggability as well as absorption, distribution, metabolism, excretion and toxicity properties of 1 were predicted. Molecular docking was applied to examine the influence of this compound on a series of the SARS-CoV-2 proteins. Compound 1 exhibited the best binding affinity with the Nsp14 (N7-MTase), Papain-like protease (PLpro) and Nsp16 (MGP site) proteins as well as demonstrated a similar efficiency toward both the native and mutated Spike proteins, RDB.
Keywords: Thiophene; synthesis; DFT; corrosion inhibitor; molecular docking; COVID-19